Role of YAP1 as a Marker of Sensitivity to Dual AKT and P70S6K Inhibition in Ovarian and Uterine Malignancies. (9th March 2017) - Previs, Rebecca A.; Armaiz-Pena, Guillermo N.; Ivan, Cristina; Dalton, Heather J.; Rupaimoole, Rajesha; Hansen, Jean M.; Lyons, Yasmin; Huang, Jie; Haemmerle, Monika; Wagner, Michael J.; Gharpure, Kshipra M.; Nagaraja, Archana S.; et al.
Abstract : Background: The PI3K/AKT/P70S6K pathway is an attractive therapeutic target in ovarian and uterine malignancies because of its high rate of deregulation and key roles in tumor growth. Here, we examined the biological effects of MSC2363318A, which is a novel inhibitor of AKT1, AKT3, and P70S6K. Methods: Orthotopic murine models of ovarian and uterine cancer were utilized to study the effect of MSC2363318A on survival and regression. For each cell line, 10 mice were treated in each of the experimental arms tested. Moreover, in vitro experiments in 21 cell lines (MTT, immunoblot analysis, plasmid transfection, reverse phase protein array [RPPA]) were carried out to characterize underlying mechanisms and potential biomarkers of response. All statistical tests were two-sided. Results: MSC2363318A decreased tumor growth and metastases in multiple murine orthotopic models of ovarian (SKOV3ip1, HeyA8, and Igrov1) and uterine (Hec1a) cancer by reducing proliferation and angiogenesis and increasing cell death. Statistically significant prolonged overall survival was achieved with combination MSC2363318A and paclitaxel in the SKUT2 (endometrioid) uterine cancer mouse model ( P <  .001). Mice treated with combination MSC2363318A and paclitaxel had the longest overall survival (mean = 104.2 days, 95% confidence interval [CI] = 97.0 to 111.4) compared with those treated with vehicle (mean = 61.9 days, 95% CI = 46.3 to 77.5), MSC2363318A alone (mean = 89.7 days, 95% CI = 83.0 to 96.4), and paclitaxel alone (mean = 73.6 days, 95% CI = 53.4 to 93.8). Regression and stabilization of established tumors in the Ishikawa (endometrioid) uterine cancer model was observed in mice treated with combination MSC2363318A and paclitaxel. Synergy between MSC2363318A and paclitaxel was observed in vitro in cell lines that had an IC50 of 5 µM or greater. RPPA results identified YAP1 as a candidate marker to predict cell lines that were most sensitive to MSC2363318A (R = 0.54, P =  .02). After establishment of a murine ovarian cancer model of adaptive anti-angiogenic resistance (SKOV3ip1-luciferase), we demonstrate that resensitization to bevacizumab occurs with the addition of MSC2363318A, resulting in improved overall survival ( P =  .01) using the Kaplan-Meier method. Mice treated with bevacizumab induction followed by MSC2363318A had the longest overall survival (mean = 66.0 days, 95% CI = 53.9 to 78.1) compared with mice treated with control (mean = 42.0 days, 95% CI = 31.4 to 52.6) and bevacizumab-sensitive mice (mean = 47.2 days; 95% CI = 37.5 to 56.9). Conclusions: MSC2363318A has therapeutic efficacy in multiple preclinical models of ovarian and uterine cancer. These findings support clinical development of a dual AKT/P70S6K inhibitor.